The Role of Plant DNA Methylation in Development, Stress Response, and Crop Breeding - Shuai Qiao; Wei Song; Wentao Hu; Fang Wang; Anzhong Liao; Wenfang Tan; Songtao Yang (Agronomy)
DNA methylation, an evolutionarily conserved epigenetic mechanism, is crucial for controlling gene activity and ensuring genomic integrity. Altered methylation patterns can profoundly affect plant development, often resulting in atypical phenotypes. The regulation of these methylation states relies on the coordinated actions of de novo methylation, maintenance, and active demethylation, orchestrated by specialized enzymes within distinct pathways. This review delves into the diverse roles of DNA methylation in plants, offering an in-depth analysis of the enzymes and regulatory factors involved. We explore how these elements function within the broader epigenetic framework, focusing on their contributions to silencing transposable elements, modulating gene expression, and shaping chromatin architecture. The review also examines the significance of DNA methylation in plant development, particularly its role in adapting to biotic and abiotic stresses. Lastly, we highlight its potential for driving innovations in crop breeding, emphasizing its applicability in advancing sustainable agriculture.